Failure mechanisms in CoCrMo modular femoral stems for revision total hip arthroplasty. Issue 6 (28th April 2016) - Wang, Qiong; Parry, Michael; Masri, Bassam A.; Duncan, Clive; Wang, Rizhi
Abstract: In this retrieval study, we reported the failure mechanisms of the CoCrMo‐based hip implants. Systematic analyses on the clinically failed modular femoral stems from Revitan™ revision prostheses revealed a multistep fracture process. Multiple microcracks were first developed under the combined action of pitting corrosion and dynamic tensile stress on the lateral side of the CoCrMo connection taper. These microcracks then served as the initiation sites of further corrosion fatigue cracking leading to the final catastrophic failure. This crack initiation process has not been previously reported on retrieved CoCrMo components and our findings provide valuable information on the clinical performance of such implants, as well as the material selection and structural designs of future modular stems. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1525–1535, 2017.